2018
DOI: 10.20450/mjcce.2018.1477
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Raman spectra of cubic form of magnesium caesium arsenate hexahydrate

Abstract: Fourier transform infrared (FT-IR) spectra recorded at room temperature (RT) and at the boiling temperature of liquid nitrogen (LNT), as well as Raman spectra recorded at room temperature for the cubic polymorph of magnesium cesium arsenate hexahydrate (MgCsAsO4·6H2O) and its partially deuterated analogues, were interpreted with respect to the normal modes of the water molecules and the arsenate ions and water librations. The spectral characteristics of MgCsAsO4·6H2O were compared to the cubic form of the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…It should be also noted that in both studied compounds, the 1(AsO4) modes appear at higher frequencies than the 3(AsO4) vibrations. The same spectral feature has been established in the vibrational spectra of orthorhombic MgNH4AsO4•6H2O and MgKAsO4•6H2O [8,9] and the cubic form of MgCsAsO4•6H2O [13], whereas for Mg2KH(AsO4)•15H2O it was found that both 1(AsO4) and 3(AsO4) modes have practically the same wavenumbers at around 830 cm -1 [11]. This finding is consistent with spectroscopic studies on different arsenate compounds (natural and synthetic) [27][28][29][30][31].…”
Section: Vibrations Of the Arsenate Ionssupporting
confidence: 88%
See 4 more Smart Citations
“…It should be also noted that in both studied compounds, the 1(AsO4) modes appear at higher frequencies than the 3(AsO4) vibrations. The same spectral feature has been established in the vibrational spectra of orthorhombic MgNH4AsO4•6H2O and MgKAsO4•6H2O [8,9] and the cubic form of MgCsAsO4•6H2O [13], whereas for Mg2KH(AsO4)•15H2O it was found that both 1(AsO4) and 3(AsO4) modes have practically the same wavenumbers at around 830 cm -1 [11]. This finding is consistent with spectroscopic studies on different arsenate compounds (natural and synthetic) [27][28][29][30][31].…”
Section: Vibrations Of the Arsenate Ionssupporting
confidence: 88%
“…However, our spectroscopic data [9] revealed that this polymorphous transition does not significantly affect the appearance of the LNT IR spectra of the potassium analogue, which are still very much alike the ones obtained for MgRbAsO4•6H2O and Mg-TlAsO4•6H2O. The identical conclusion has been deduced for the spectra of the other related com-pounds with formula M I M II XO4•6H2O (M I = NH4, K, Rb, Cs, Tl; M II = Mg, Co, Ni; X= P, As) no matter if they crystallize in the orthorhombic, hexagonal, cubic or monoclinic system and/or correspondingly they have four, two or one crystallographically different water molecules of crystallization in their structure [8,9,13,[18][19][20][21][22][23][24][25]. The only difference that is evident in these spectra is in the region of the HOH librations and is dependent on the number of the crystallographically different water molecules of crystallization that exist in the structure and the type of the anion (phosphate or arsenate).…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations